Ketidakhadiran Negara dan Ketahanan Ekonomi Ilegal: State Fragility di Pedesaan Kolombia - M. Rezky Fatiha Thamrin; Imam Fadhil Nugraha (Jurnal Ilmiah Hubungan Internasional Fajar, 2026)
This study explores how the structural absence of the state facilitates the persistence of illegal economic activities through governance mechanisms that exclude the state in rural areas of Colombia. Although Colombia has a globally recognized democratic system of government, the state has consistently failed to establish a tangible presence in remote areas. For years, these regions have been dominated by various armed groups such as the Revolutionary Armed Forces of Colombia (FARC) and the National Liberation Army (ELN). Using a qualitative approach focused on library research, this study combines three main analytical frameworks: state instability, non-state governance, and the illegal economy as a resilience system. The research findings indicate that the absence of the state in rural Colombia is not merely due to the lack of public services. It is also a condition actively shaped by historical political decisions that have neglected peripheral regions. These structural conditions create an opening that armed groups systematically exploit by offering an effective alternative form of governance, while the coca economy serves as the material foundation that continuously reinforces and perpetuates this cycle. This explains why interventions that focus solely on a single aspect of the cycle never yield significant structural change. Keywords: State Fragility, State Absence, Illegal Economy, Non-State Governance, Colombia